The bug club - Gravel, Elise (Drawn & Quarterly, 2021)
"Informative and fun book on bugs: In The Bug Club, Elise Gravel shares all her favourite and most interesting facts about these marvelous creatures, some of which are so unique and strange, you could almost imagine them living in outer space!"--